An error in temporal error theory - Tallant, Jonathan (Cambridge University Press, 2018)
Within the philosophy of time there has been a growing interest in positions that deny the reality of time. Those positions, whether motivated by arguments from physics or metaphysics, have a shared conclusion: time is not real. What has not been made wholly clear, however, is exactly what it entails to deny the reality of time. Time is unreal, sure. But what does that mean?